2022
DOI: 10.3390/s22072516
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Metal Based Nano-Composites for Printable Stretchable Electronics

Abstract: Liquid metal (LM) has attracted prominent attention for stretchable and elastic electronics applications due to its exceptional fluidity and conductivity at room temperature. Despite progress in this field, a great disparity remains between material fabrication and practical applications on account of the high surface tension and unavoidable oxidation of LM. Here, the composition and nanolization of liquid metal can be envisioned as effective solutions to the processibility–performance dilemma caused by high s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 102 publications
0
9
0
Order By: Relevance
“…Micro-and nano-sized LM droplets are fabricated to realize easier access to the application of LM [68]. The size of LM can be regulated by the fabrication methods, including inkjet directly, inkjet in solution, mechanical stirring, atomization process, ultrasonic treatment, thermal evaporation, etc.…”
Section: Strechable Composites With Micro-or Nano-sized Lmmentioning
confidence: 99%
“…Micro-and nano-sized LM droplets are fabricated to realize easier access to the application of LM [68]. The size of LM can be regulated by the fabrication methods, including inkjet directly, inkjet in solution, mechanical stirring, atomization process, ultrasonic treatment, thermal evaporation, etc.…”
Section: Strechable Composites With Micro-or Nano-sized Lmmentioning
confidence: 99%
“…In recent years, due to the excellent features realized by adding elements, a variety of heterophasic LMs have been introduced into different fields such as soft electronics, magnetic robots, catalysis, energy management, and biomedical applications [43,53–56] . This review intends to classify the recent research about heterophasic LMs through a fresh and practical perspective of elements and functionalities (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…[51,52] In recent years, due to the excellent features realized by adding elements, a variety of heterophasic LMs have been introduced into different fields such as soft electronics, magnetic robots, catalysis, energy management, and biomedical applications. [43,[53][54][55][56] This review intends to classify the recent research about heterophasic LMs through a fresh and practical perspective of elements and functionalities (Figure 1). According to the functionalities derived from different metallic elements, heterophasic LMs are systematically organized into four categories in the review as shown in Figure 1b and Table 1.…”
mentioning
confidence: 99%
“…Liquid metal has excellent conductivity, deformability, and biocompatibility, which is very suitable for the application of wearable electronics, electronic skin, soft robot sensors, electronic tattoos, and sensors for VR/AR globe sensors . Recently, liquid metal-based flexible sensors have received widespread attention due to their superior sensing performance and applications. Liquid metal-based sensors can be roughly divided into the following: first, flexible sensors prepared by mixing a liquid metal with a flexible substrate; second, a flexible sensor that sprays or prints liquid metal onto a flexible substrate surface; third, a flexible sensor that fills a flexible substrate microchannel with liquid metal. The liquid metal-filled microchannel sensor is attractive due to its simple preparation method and easy recovery of liquid metal . Regarding the liquid metal-filled microchannel sensor, elastic polymer materials are usually used as flexible substrates for embedded microchannels, making the sensor highly flexible and elastic.…”
Section: Introductionmentioning
confidence: 99%